1989
DOI: 10.1007/bf02553817
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sucralfate on experimental colitis in the rat

Abstract: The therapeutic effect of sucralfate on ulcerated gastric and duodenal mucosa is well known. There is, however, almost no information about its activity in colitis. Experimental colitis was produced in rats by rectal instillation of 1 ml of 10 percent acetic acid, and 1.5 ml of a 20 percent suspension of sucralfate was then administered every 12 hours for various lengths of time. Study animals and appropriate controls were killed after 3, 7, 10, or 14 days. The distal colons were studied macroscopically and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
1
10
0
1
Order By: Relevance
“…Despite these aspects our findings were similar to those found by other authors who evaluated the effects of SCF on chemically-induced colitis model 41 . In the animals from the group where intervention was performed with saline, the epithelial surface was irregular, with a…”
Section: Evaluation Of the Application Of Enemas Containing Sucralfatsupporting
confidence: 92%
“…Despite these aspects our findings were similar to those found by other authors who evaluated the effects of SCF on chemically-induced colitis model 41 . In the animals from the group where intervention was performed with saline, the epithelial surface was irregular, with a…”
Section: Evaluation Of the Application Of Enemas Containing Sucralfatsupporting
confidence: 92%
“…The laboratory findings on the biopsy specimen suggested that sucralfate acts as a scavenger of highly reactive oxygen metabolites and is the effective drug in reducing radiation-induced esophagitis. For the cytoprotective action of sucralfate, the following mechanisms were implicated (37)(38)(39)(40): protection of blood vessels, promotion of epithelial regeneration by protecting and stimulating the mucosal proliferation zone, and stimulation of growth factors such as epidermal growth factor. Kochhar et al (23,41) were the first to show good results in controlling rectal bleeding with rectally administered sucralfate.…”
Section: Managementmentioning
confidence: 99%
“…Zahavi/Burg/Marcus/Karmeli/Nusinovitz/ De-Nol in Experimental Colitis Dinari Colonic prostaglandin levels are increased in active ulcerative colitis [16,17], and are decreased by therapeu tically effective drugs such as steroids, sulfasalazine, and sucralfate [21,22]. In the present study, CBS enemas sim ilarly reduced the elevated PGEr levels induced by acetic acid administration.…”
mentioning
confidence: 54%
“…The morphologic features include multiple mucosal erosions and ulcers, accompa nied by severe inflammatory reaction and crypt abscesses, thus resembling human colitis [20,21], CBS enemas caused gross and histologic improvement in our animal model, evident even after a short treatment period of 5 days.…”
Section: Discussionmentioning
confidence: 96%